Representações de federalismo e sistema nacional de educação no pensamento de Rui Barbosa - Silva, Hebert Santos da (2018)
This dissertation aimed to analyze how Rui Barbosa reconciled the defense of the adoption of the federative state with the idea of forming a national education system in Brazil in the second half of the nineteenth century. To do so, we discuss the representations made about Rui Barbosa's educational and federative thinking, we relate the trajectory of the author's thought and its social place with his conceptions about administrative decentralization of the State and centralization of the organization of public instruction, in order to perceive the representations made by Rui Barbosa on the situation of teaching in Brazil in his writings. As a research of a historiographical nature, the volumes IX (volume I) and X (volume I to IV) of the Complete Works of Rui Barbosa were used as primary sources, because they contained the famous opinions on the Reformation of Secondary and Higher Education and the Reform of Primary Education and several Supplementary Institutions of Public Instruction, respectively. In addition to the cited volumes, we also work with the work Queda do Império, as a source of the justificatory arguments of the author's federalist opinion. Such documentary analyzes in the light of French Cultural History and the notions of representation and social place served as a contribution to answer our main research question: how does Rui Barbosa reconcile the concepts of federalism and national education system in his writings? With this question, we analyze the sources, arriving at the conclusion that both federalism and the adoption of a national education system are part of the same conservative modernization project proposed by Rui Barbosa for Brazilian society.